Election, Atonement, and the Holy Spirit : Through and beyond Barth's Theological Interpretation of Scripture - Grebe, Matthias (Cambridge : James Clarke & Co., 2015)
Election, Atonement, and the Holy Spirit' is an examination of the doctrines of election and atonement in Karl Barth's 'Church Dogmatics', taking up Barth's own challenge to his reader to surpass his argument and offer a better typological interpretation of the cultic texts. Barth's radical re-working of Calvin's doctrine of election is one of the most important developments in twentieth-century theology. Christ synthesizes for Barth a particular dialectic: the binary structure of God's Yes of election and God's No of rejection. The book's central question - how can Jesus simultaneously be bot.
4: Jesus the High Priest5: Jesus is Victor: The Conquering of Sin; 6: Existenzstellvertretung in the New Testament; Conclusion; 5. Election, Atonement, and the Holy Spirit; Introduction; 1: Election and Universalism; 2: The Eternal Spirit and the Mortal Soul; 3: Humanity, Freedom, and Faith; Conclusion; Conclusion; 1: Problems with Barth's Exegesis; 2: Beyond the Binary Impasse of the Yes and No in Christ; 3: Pastoral Implications: Limited Atonement and Universalism; 4: Systematic Implications: The Economic and Immanent Trinity; Concluding Remarks; Bibliography; Back cover
Includes bibliographical references.
Vendor-supplied metadata.
Keywords: Barth, Karl, -- 1886-1968 -- Criticism and interpretation; Election (Theology) -- History of doctrines -- 20th century; Atonement; Holy Spirit; Bible -- Hermeneutics; RELIGION / Christian Theology / Anthropology; Barth, Karl, 1886-1968--Criticism and interpretation; Bible; Bible--Hermeneutics.; Barth, Karl, -- 1886-1968.; Bible; Atonement; Election (Theology) -- History of doctrines; Hermeneutics; Holy Spirit; RELIGION / Christian Theology / Systematic; 1900-1999; Electronic books; Criticism, interpretation, etc